A novel nucleotide insertion in S gene of hepatitis B virus in a chronic carrier - He Shusen; He Jilan; Sun Li; Tong Wenbin; Du Fei (Virology Journal, 2010)
Abstract Hepatitis B virus DNA was extracted from serum of a chronic carrier and polymerase chain reaction was performed on S gene. Direct sequencing showed a variant HBsAg with additional 4-amino acid insertion, and clone sequencing confirmed the mixture of variant HBsAg and wildtype HBsAg. Of 16 clones with 12-nucleotide insertion, 15 clones had identical AGAACAACACAA insertion between nucleotide 494 and nucleotide 495, and one clone had GGAACAACTCAA insertion in the same position plus 3-nucleotide deletion from nucleotide 491 to nucleotide 493. S114T, C121Y, T126S/A, Q129K, G130R, T131N, M133T, G145R, N146D substitution and premature stop codon were also found in those clones. However, the origin of HBV with 4-amino acid insertion in HBsAg was unclear.